2018
DOI: 10.1016/j.toxrep.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Co-exposure to titanium dioxide nanoparticles (NpTiO2) and lead at environmentally relevant concentrations in the Neotropical fish species Hoplias intermedius

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 86 publications
(122 reference statements)
2
7
0
Order By: Relevance
“…Noman et al [ 24 ] and Nyamukamba et al [ 25 ] described in detail the crystalline structure of anatase and rutile and the differences in their properties in their overview papers. The results of a morphology test of a sample of TiO 2 with the catalogue number 637254 carried out by Vicari et al [ 26 ] confirmed our presumption that anatase was spherical/oval particles. Despite the presence of impurity being rutile in the TiO 2 NPs sample, the specific surface area result obtained by us (81.6 m 2 /g) was very similar to the test results obtained by Vicari et al [ 26 ] (83.5 m 2 /g), who used an analogous sample of TiO 2 with the catalogue number 637254 in their tests.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Noman et al [ 24 ] and Nyamukamba et al [ 25 ] described in detail the crystalline structure of anatase and rutile and the differences in their properties in their overview papers. The results of a morphology test of a sample of TiO 2 with the catalogue number 637254 carried out by Vicari et al [ 26 ] confirmed our presumption that anatase was spherical/oval particles. Despite the presence of impurity being rutile in the TiO 2 NPs sample, the specific surface area result obtained by us (81.6 m 2 /g) was very similar to the test results obtained by Vicari et al [ 26 ] (83.5 m 2 /g), who used an analogous sample of TiO 2 with the catalogue number 637254 in their tests.…”
Section: Discussionsupporting
confidence: 75%
“…The results of a morphology test of a sample of TiO 2 with the catalogue number 637254 carried out by Vicari et al [ 26 ] confirmed our presumption that anatase was spherical/oval particles. Despite the presence of impurity being rutile in the TiO 2 NPs sample, the specific surface area result obtained by us (81.6 m 2 /g) was very similar to the test results obtained by Vicari et al [ 26 ] (83.5 m 2 /g), who used an analogous sample of TiO 2 with the catalogue number 637254 in their tests. According to the producer’s data, the specific surface area of the TiO 2 NPs sample that we purchased should range from 45 m 2 /g to 55 m 2 /g [ 23 ], which is reported also, e.g., by Fiorenza et al [ 27 ] in their paper.…”
Section: Discussionsupporting
confidence: 75%
“…On the opposite, TiO 2 NPs under UV light induced significant NAs at 10 mg L À1 . In addition, Vicari et al (2018) observed no significant increase in piscine MN in Hoplicus intermedius exposed to TiO 2 NPs (100% anatase) at 100 mg L À1 . Differences in results may most likely be due to the fish species utilized and different experimental conditions, such as illumination.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, no neurological disturbances of the cholinergic system were found in the brain after IP injection of TiO 2 NPs and BP-3, isolated or in mixture, for 3 and 7 days. In the same direction, several studies with freshwater fish reported no alterations in the AChE activity in the brain after waterborne exposure to TiO 2 NPs [46,[80][81][82][83]. On the contrary, waterborne exposure of the freshwater fish Carassius auratus to 200 µg L −1 of BP-3 promoted the increase in the activity of AChE [84].…”
Section: Neurotoxicitymentioning
confidence: 92%